2009
DOI: 10.1182/blood.v114.22.1052.1052
|View full text |Cite
|
Sign up to set email alerts
|

High Remission Rates and Long-Term Survival in a High Percentage of Patients Achieved by Intensive Chemotherapy for AML and Further Improvement of Supportive Care.

Abstract: 1052 Poster Board I-74 Background: Until recently, intensive chemotherapy for acute myeloid leukemia (AML) did not necessarily lead to high success rates, partly because of deaths from infections due to the associated long-term neutropenic phase. However, the advent of effective antifungal agents or the use of granulocyte colony-stimulating factor (G-CSF) or macrophage colony-stimulating factor (M-CSF) has definitely reduced deaths from chemoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The patients with good or intermediate risk factors had remarkable improvements. The study showed that the treatment is effective and safe [ 47 ] (Table 6 ).…”
Section: New Agentsmentioning
confidence: 99%
“…The patients with good or intermediate risk factors had remarkable improvements. The study showed that the treatment is effective and safe [ 47 ] (Table 6 ).…”
Section: New Agentsmentioning
confidence: 99%
“…She was diagnosed with AML classified as normal karyotype and Intermediate-II genetic group according to the criteria of European Leukemia Net [10] . After achieving complete remission by induction chemotherapy containing idarubicin, enocitabine, 6-mercaptopurine, and predonisolone [11] , she received high-dose cytarabine therapy as post-remission therapy from day + 41. Voriconazole at 400 mg/day was used for fungal prophylaxis during induction and consolidation therapy.…”
Section: Casementioning
confidence: 99%